The Effect of Wood Java Leaf Hay on Weight and Local Goat Carcass Percentage - Rahmat, Rahmat; Mulyati, Mulyati (FAPETKAN UNTAD, 2020)
This study aims to determine the ratio of weight and carcass percentage of local goats that are given and not given Java wood hay. The research material was 12 female Kacang goats aged 10 months. The study used a comparative test method between two treatments, each of which was repeated 6 times. The treatments of the research were P1 = Giving concentration of 1.0% BK from BB without leaves of Java wood and P2 = Giving concentration of 1.0% BK from BB + hay from Java wood leaves 0.5% BK from BW. The results showed that the carcass weight of the bean goat carcass (P1 = 7.02 and P2 = 7.35) which were given the concentrate without the leaves of Javanese wood (P1) and those which were given the concentrate + hay of the leaves of the Java wood and (P2) were not significantly different (P> 0.05). . The percentage of peanut goat carcass (P1 = 46.60 and P2 = 48.26) showed that the provision of concentrate without hay of Java wood leaves was significantly lower than the percentage of carcass of peanut goat carcass which was given concentrate + hay of Java wood leaves at the 95% confidence level.